L’anacarde : produit de la globalisation, moteur de la territorialisation, l’exemple du Sud du Burkina Faso - Sarah Audouin; Alexis Gonin (EchoGéo)
The rise of cashew nut in Burkina Faso was strongly supported by the State in the 1980s, through conservation territories, later turned into development territories. But from 1995, the globalization of trade led to a restructuration of the value chain. The expansion of cashew nut orchards became the fact of individual farmers. Introduction and diffusion of the orchards go along, at local scale, with land right renegotiation. During this re-territorialization, some gain rights while others lose. This socio-spatial reconfiguration, led by international trade, raise the question of long term effects of this bottom-up territorialization, which turns out to be unequal.